กระบวนการแก้ไขปัญหาชีวิตด้านเศรษฐกิจโดยใช้หลักธรรมทางพุทธศาสนา - แก้วขำ(Pimwimol Kaewkham) พิมพ์วิมล; ธนะชานันท์(Supaporn Thanachanan) สุภาพร (Journal of Behavioral Science for Development, 2016)
(Life Problem-Solving Process in Part of Economic Problems by Using the Buddhist Dharma Principles) Abstract The objectives of this research were to study the causes of economically life problems, the solution methods by using the Buddhist dharma principles and the result gathered from six sample persons using those solution methods to cure their problems. This research had been done through the intensive interview as well as the observation. The results of this research are as follows; The main causes of economically life problems can be elaborated to two reasons. 1) Individually mindset rooted from bad attitude lead to crave for sensual pleasure in either invaluable or ephemeral things. It can be also rooted from lacking of self-respect or self-assurance. 2) Social and environment caused by economic problems in specified period lead to deprived and impecunious situation. In addition, to be admired by both social and friend is always the pressure and leads to economically life problems. The Buddhist dharma principles used as the solution methods are the four Noble Truths which will be applied with the rule of Critical Reflection (Yonisomanasikara). The processes for this solution are as follows; 1) the problem must be realized and diagnosed. This means the implication to himself/herself and his/her family must be realized. 2) The root of problem must be found out through critical thinking process, asking question regarding to both controllable (the profusion) and causes (economic problem of the country or international). 3) Goal for curing the problem must be set by separating into short-term solution, which will relieve and restrain the problem, and long-term solution, which removes entire problems. 4) problem solving must be engrossed in, which covers (1) behavior approach by self-controlling, (2) mental approach by practicing to have mental strength and not be infatuated in seducing matter and (3) wisdom approach by changing attitude, vision and aspect in order to understand the right and suitable living by not follow social environment or materialism. Furthermore, it is indispensable to understand the nature uncertainty. And the study has shown that the support from family and relative person is important for the right solution. They will support, will be closely and will be courage to the person facing with the problem until the problem has already been solved. The result from using the dharma principles as the solution methods in economically life problem are as follows; 1) Dharma is able to be as method to solve the problem immediately. It means that mental problem has been cured, that person let himself on and that the stress will be decreased. 2) The problems can be solved for long term. 3) The systemic thinking by considering the overall perspective, looking through the problem and future alteration will be increased. 4) Dharma can be applied for solving other life issues. 5) There will be immunity in case of facing with the problem in the future. Keywords: Life Problem-Solving, the Buddhist Dharma Principles